Lead poisoning from an unexpected source in a 4-month-old infant. - Shannon, M (1998)
Childhood lead poisoning is characteristically a disease that occurs between the second and third years of life, generally resulting from the child's ingestion of lead-based paint or dust. However, lead poisoning may also appear in the first year of life. The case of a 4-month-old infant is reported in which the preparation of infant formula in a lead-soldered samovar (urn) resulted in venous blood lead levels as high as 46 microg/dl. The samovar had been brought into the United States by the parents while on a visit to Iran. The infant was placed on chelation therapy with parenteral CaNa2EDTA followed by oral meso-2,3-dimercaptosuccinic acid (DMSA) and d-penicillamine. This resulted in a rapid and substantial reduction in the blood lead level. Lead poisoning in infancy may have unusual etiologies such as in utero transmission of lead by lead-poisoned women. Because sources of lead poisoning in infancy may be unusual, a detailed environmental investigation may be necessary to identify the exact source. Children exposed to lead in the first 2 years of life have a special vulnerability to the neurotoxicity of lead, with the risk of enduring developmental handicaps. Continued public health initiatives to remove lead from the environment, in conjunction with routine lead screening of young children, will be key in meeting the goal of the Centers for Disease Control and Prevention to eliminate childhood lead poisoning by the year 2011.